O papel do direito nas teorias da justiça de John Rawls e Amartya Sen - Lima, André Canuto de Figueiredo (2021)
This dissertation investigates the role attributed to law by the theories of justice developed by John Rawls and Amartya Sen. The starting point is Rawls' seminal work “A Theory of Justice”. Although Sen did not fully adhere to and continue the work of Rawls, due to methodological differences, there is declared agreement regarding the priority of freedom. The work thus explores the principles of freedom and equality from the perspective of both authors - the choice procedure indicated by Rawls, Sen's criticisms of this format and also the definition of primary goods as an alternative to solving the problem of the distributive issue. The different theoretical perspectives of each philosopher are also presented, both affiliated to the political form of justice: Rawls' option for renewed contractualism, Sen's adoption of the comparative method inspired by Adam Smith and the influence of social choice theory on Sen's thinking. As for the law, its function refers to the protection and enforcement of basic freedoms. Therefore, the authors define that the justice model is only compatible with democracies, especially those that are guided by the primacy of constitutional norms. Finally, specific aspects of the two philosophers' view of law, but compatible with each other, are analyzed, such as the relationship between the rule of law and formal justice, and the importance of human rights for the realization of justice.